ANALISIS KEKERABATAN BEBERAPA TANAMAN MANGGA (Mangifera spp.) BERDASARKAN KARAKTERISTIK MORFOLOGI DAN ANATOMI DAUN - Melandani, Luh Putu; Kriswiyanti, Eniek; Ria Defiani, Made (SIMBIOSIS, 2017)
ABSTRACT The study was aimed to explore the characteristics of morphological, anatomical, and phylogenetic relationship between some types of mango (Mangifera sp.). Research conducted in Structures Laboratory of Plant Development Department of Biological Science, University of Udayana from April 2015 - July 2015. Samples were taken from three districts in Bali, that Denpasar, Gianyar and Badung. Ten species of plants of mango (Mangifera indica : ‘poh arum manis’, ‘poh bukit’, ‘poh gedang’, ‘poh madu’, ‘poh apel’, ‘poh golek’, ‘poh sambuk’, ‘poh bali’, ‘poh manalagi’) and Wani (Mangifera caesia.) shows the character of morphology and anatomy of leaves varies as well as the analysis of kinship showed ten types of mangoes grouped into two major groups based on the degree of similarity. Fenogram shows the level of similarity of the ten types of mangoes in Bali grouped (cluster) into two: group I ‘poh arum manis’, ‘poh bukit’, ‘poh gedang’, ‘poh bali’, ‘poh apel’, and group II, namely ‘poh madu’, ‘wani’, ‘poh golek’, ‘poh sambuk’, ‘poh manalagi’ where two clusters have a degree of similarity ? 63.91%.